The utilization of Public-Private- Partnerships in schools: PPP Experiences From Tigania West sub-county,Kenya. - Kubaison, Simon (African Journal of Science, Technology and Social Sciences, 2022)
This is a preliminary study on public-private partnerships in public secondary schools in Tigania west Sub-county.The Objective of the study was to Investigate the models of public-private partnerships available in public secondary schools in Tigania West sub-county. The study was conducted in 46 public secondary schools between September and December 2021. The main data collection instruments comprised an observation checklist and Interview schedules. School managers, KEPSA, and Ministry of Education officials provided interviews. Key findings include low levels of PPP intake in schools, poor performance in examinations, dilapidated infrastructure, under-utilization of certain facilities, lack of initiativeness by school managers, and lack of policy guide from MOE on implementation of PPPs in schools. The key PPP model preferred in schools was Annuity payment, followed by PFI. The study recommends decentralization of PPP projects and authority in the education sector to aid school management benefit from the PPP Act of 2013.